Universities in the Process of Reforming - Jucevičienė, Palmira (Acta Paedagogica Vilnensia, 1996)
The second half of the 20th century is known as a period of intense reforming of higher education. The main reason for the modernization of higher education is forming of the post-industrial environment. The article discusses basic principles of the modernization of higher education and most important features of the modem university. Activities of modernization of universities are also discussed in the organizational context Theory of learning organizations might be useful for better understanding of the process. The main idea of the theory and the definition of learning organization is presented in the article, as well as its basic characteristics. Faculty of Administration of Kaunas University of Technology is presented as an example of contemporary academic structure becoming a learning organization. Results of the research conducted in the Faculty are presented in the final chapter of the article.
Keywords: University; reforming of higher education; modernization; theory of learning; learning organization.